Floristic composition of river Ilo-Moquegua basin and Lomas of Ilo, Moquegua, Peru - Arakaki, Mónica (2003)
A study of the vascular flora composition in the river Ilo-Moquegua basin and Lomas of Ilo is presented herein, at elevations that vary between sea level and 4600 meters, based on intensive collections, examination of herbarium specimens and bibliographic research. According to the present study, the vascular flora in the river Ilo-Moquegua basin and Lomas of Ilo was found to consist of 63 families, 233 genera and 394 species. Eighty three percent of the species are Magnoliopsida and 15% belong to the Liliopsida. Families with the largest number of genera and species are Asteraceae (41 genera and 60 species), Poaceae (28 and 44), Solanaceae (11 and 32), Fabaceae (17 and 26), Malvaceae (11 and 21), Brassicaceae (10 and 15), Boraginaceae (9 and 15) and Cactaceae (10 and 14). The dominant biological forms are herbs (69%), followed by shrubs (28%), climbing plants (4%), trees (2%) and parasitic plants (less than 1%). Fifty five species are endemic to Peru, and 10 are restricted to the department of Moquegua. Total of 176 new additions for the department of Moquegua are presented.